Rotas tecnológicas dos resíduos sólidos em comunidades quilombolas do lago de Tucuruí-PA - SOUZA, Alana de Almeida (2024)
Inadequate management of solid waste causes several socio-environmental problems, which are recurrent in rural areas, especially in traditional communities. The objective of this study is to map the descriptive technological routes of domestic waste - specifically recyclable, organic and dangerous - from two quilombola communities on the Tucuruí side: Crioulas and Jutaí, both in Breu Branco, Pará. To this end, the research was carried out in three stages: preparation and application of the research instrument; collection, compilation and analysis of data; and, finally, mapping of descriptive technological routes. The results showed similar technological routes in both communities, characterized by the non-segregation of waste on site, the limitation of differentiated collection and transportation and burning as the main form of inadequate treatment of the waste generated. On the other hand, the metals are segregated and collected by a scrap yard, being taken to a sorting center and subsequently sold to recycling industries.